Hydrogen fuel cell stainless steel bipolar plate surface composite coating and preparation method thereof
By depositing a multilayered CrN/Cr/CrN coating with a multilayer structure on the surface of the stainless steel bipolar plate, the corrosion resistance and conductivity problems in the acidic environment of hydrogen fuel cells are solved, and the corrosion resistance and conductivity are significantly improved. , extends service life and improves the power density of hydrogen fuel cells.
Patent Information
- Application Number
- CN202411255963.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-07
AI Technical Summary
Stainless steel bipolar plates have poor corrosion resistance and insufficient conductivity in the acidic environment of hydrogen fuel cells, resulting in reduced power density and short service life.
The metal Cr transition layer, CrN bottom layer, metal Cr intermediate layer and CrN surface layer were deposited successively on the surface of the stainless steel bipolar plate. The composite coating with multilayer structure was formed by physical vapor deposition combined with cathode arc + glow discharge technology.
It significantly improves the corrosion resistance and conductivity of stainless steel bipolar plates, reduces corrosion rate and interface contact resistance, extends service life, and improves the power density of hydrogen fuel cells.
Smart Images

Figure CN119275305A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy fuel cells, and in particular to a composite coating on the surface of a stainless steel bipolar plate of a hydrogen fuel cell and a preparation method thereof. Background Art
[0002] In recent years, due to the depletion of fossil energy and the increasing severity of environmental pollution, the development of renewable energy technology is of great significance to the sustainable development of society. Hydrogen fuel cells can directly convert chemical energy in fuel into electrical energy. They are considered to be the most promising energy device of the next generation and are receiving more and more attention from academia and industry. Hydrogen fuel cells have the advantages of fast start-up, high conversion efficiency, high power density, and low-temperature operation. They can be widely used in fixed power stations, portable power supplies, transportation vehicles, national defense and military fields. Especially in the automotive field, proton exchange membrane fuel cells are favored by major automobile manufacturers. Major domestic and foreign automobile manufacturers such as Toyota of Japan, Mercedes-Benz of Germany, General Motors of the United States, and SAIC Passenger Vehicles have invested heavily in fuel cell vehicle technology research and development and launched their own models.
[0003] Bipolar plate is one of the core components in hydrogen fuel cells, accounting for 80% of the weight of the battery and 20%-30% of the cost. It mainly collects electrons, distributes reaction gases, discharges reaction generated water, supports membrane electrodes, etc. Therefore, from a technical point of view, the bipolar plate material needs to have high conductivity, good mechanical properties and gas permeability resistance. The inside of a hydrogen fuel cell is a high temperature (60-95℃), high humidity, acidic (pH 3-5) corrosive environment, so the bipolar plate material is required to have strong corrosion resistance. The corrosion resistance of bipolar plate materials is one of the key factors affecting the life of hydrogen fuel cells. At present, the bipolar plate materials used in PEMFCs are mainly carbon-based materials and metal materials. Graphite materials have good chemical stability, strong conductivity, and high corrosion resistance. They are ideal materials for the early preparation of bipolar plates. However, the poor machinability, poor vibration resistance, high manufacturing cost, and easy gas permeability of graphite materials limit their commercial application.
[0004] In recent years, stainless steel has become an ideal material for metal bipolar plates due to its superior forming properties, high mechanical strength, good vibration resistance and gas permeation resistance, and has received increasing attention. However, the corrosion of stainless steel in the hydrogen fuel cell environment will block the proton exchange membrane, contaminate the catalyst, and increase the contact resistance between the bipolar plate and the gas diffusion layer, which can easily lead to a reduction in the power density of the hydrogen fuel cell. Summary of the invention
[0005] The purpose of the present invention is to provide a composite coating on the surface of a hydrogen fuel cell stainless steel bipolar plate and a preparation method thereof, so as to enhance the corrosion resistance and electrical conductivity of the stainless steel bipolar plate.
[0006] The purpose of the present invention can be achieved through the following technical scheme: a composite coating on the surface of a hydrogen fuel cell stainless steel bipolar plate, comprising a metal Cr transition layer, a CrN bottom layer, a metal Cr intermediate layer, and a CrN surface layer sequentially arranged on the stainless steel bipolar plate.
[0007] Preferably, the thickness of the metal Cr transition layer is 0.08-0.13 μm, the thickness of the CrN bottom layer is 0.35-0.45 μm, the thickness of the metal Cr intermediate layer is 0.32-0.44 μm, and the thickness of the CrN surface layer is 0.35-0.45 μm.
[0008] A method for preparing the composite coating on the surface of the above-mentioned hydrogen fuel cell stainless steel bipolar plate, which sequentially deposits a metal Cr transition layer, a CrN bottom layer, a metal Cr middle layer, and a CrN surface layer on the stainless steel bipolar plate by physical vapor deposition.
[0009] Preferably, the stainless steel bipolar plate is sequentially subjected to surface pretreatment and ion etching cleaning before coating deposition.
[0010] Further preferably, the surface pretreatment comprises the following steps:
[0011] (11) preparing an aqueous solution containing 0.15 wt % to 0.3 wt % of potassium phosphate, 0.2 wt % to 0.3 wt % of triethanolamine, and 0.15 wt % to 0.3 wt % of fatty acid polyoxyethylene ester;
[0012] (12) heating the prepared aqueous solution to 50° C.-60° C.;
[0013] (13) Immerse the stainless steel bipolar plate in the prepared aqueous solution and perform ultrasonic cleaning for 20 min to 30 min to remove surface adhesives;
[0014] (14) After ultrasonic cleaning, immerse the stainless steel bipolar plate in deionized water at 50° C. to 60° C. and perform ultrasonic oscillation cleaning on the plate for 20 min to 30 min to remove the residual aqueous solution on the surface.
[0015] (15) Take out the stainless steel bipolar plate, quickly remove water stains on its surface and dry it.
[0016] More preferably, in the aqueous solution of step (11), the concentration of potassium phosphate is 0.2 wt %, the concentration of triethanolamine is 0.25 wt %, and the concentration of fatty acid polyoxyethylene ester is 0.2 wt %.
[0017] More preferably, step (12) heats the aqueous solution to 60°C.
[0018] More preferably, the ultrasonic oscillation cleaning time in step (13) is 30 minutes.
[0019] More preferably, in step (14), the temperature of the deionized water is 50° C. and the ultrasonic oscillation cleaning time is 20 min.
[0020] Further preferably, the ion etching cleaning comprises the following steps:
[0021] (21) Clamping the surface pretreated stainless steel bipolar plate into the coating chamber, with the stainless steel bipolar plate being 15 to 20 cm away from the coating target;
[0022] (22) reducing the vacuum degree of the coating chamber to below 0.5 Pa;
[0023] (23) heating the stainless steel bipolar plate to 300-350° C.;
[0024] (24) introducing argon gas at a flow rate of 120 sccm to 150 sccm into the coating chamber, setting the negative bias voltage of the argon glow discharge to 700 V to 800 V, setting the current of the Cr target arc discharge to 120 A to 150 A, and setting the current of the magnetic field coil to 7 A to 9 A;
[0025] (25) Ion etching for 25 min to 30 min.
[0026] More preferably, in step (21), the distance between the stainless steel bipolar plate and the coating target is fixed at 15 cm.
[0027] More preferably, in step (22), the vacuum degree of the coating chamber is reduced to 0.4 Pa.
[0028] More preferably, in step (23), the stainless steel bipolar plate is heated to 350°C.
[0029] More preferably, in step (24), the flow rate of argon gas is 140 sccm, the negative bias voltage of the glow discharge is 800 V, the current of the Cr target arc discharge is 130 A, and the magnetic field coil current is set to 8 A.
[0030] More preferably, the ion etching time in step (25) is 25 minutes.
[0031] Preferably, the composite coating is prepared by cathode arc + glow discharge technology.
[0032] Preferably, the raw materials required for preparing the composite coating are argon (Ar) and nitrogen (N2) with a purity of 99.99%, and a metal Cr target with a purity of 99.95%.
[0033] Preferably, the deposition process of the metal Cr transition layer comprises the following steps:
[0034] (31) The stainless steel bipolar plate is maintained at 300-350° C., argon gas with a flow rate of 80 sccm-100 sccm is introduced into the coating chamber, the negative bias voltage of the argon glow discharge is set to 190 V-210 V, the current of the Cr target arc discharge is set to 100 A-120 A, and the magnetic field coil current is set to 4 A-6 A;
[0035] (32) A metal Cr transition layer is deposited on the surface of the stainless steel bipolar plate for 10 min to 15 min.
[0036] Further preferably, in step (31), the stainless steel bipolar plate is maintained at 350° C., the argon flow rate is 90 sccm, the negative bias voltage of the argon glow discharge is 200 V, the current of the Cr target arc discharge is 110 A, and the magnetic field coil current is 6 A.
[0037] Further preferably, in step (32), the deposition time of the metal Cr transition layer is 10 min.
[0038] Preferably, the deposition process of the CrN bottom layer comprises the following steps:
[0039] (41) The stainless steel bipolar plate with a metal Cr transition layer deposited on the surface is maintained at 300-350° C., and nitrogen gas with a flow rate of 90 sccm-120 sccm is introduced into the coating chamber. The negative bias voltage of the nitrogen glow discharge is set to 110 V-130 V, the current of the Cr target arc discharge is set to 110 A-130 A, and the current of the magnetic field coil is set to 4 A-6 A;
[0040] (42) Deposit a CrN base layer on the surface of the metal Cr transition layer for 35 min to 45 min.
[0041] Further preferably, in step (41), the stainless steel bipolar plate is maintained at 350° C., the nitrogen flow rate is 110 sccm, the negative bias voltage of the nitrogen glow discharge is 120 V, the current of the Cr target arc discharge is 120 A, and the magnetic field coil current is 6 A.
[0042] Further preferably, the deposition time of the CrN bottom layer in step (42) is 40 minutes.
[0043] Preferably, the deposition process of the metal Cr intermediate layer comprises the following steps:
[0044] (51) The stainless steel bipolar plate with a metal Cr transition layer and a CrN bottom layer deposited on the surface is maintained at 300-350° C. Argon gas with a flow rate of 100 sccm-120 sccm is introduced into the coating chamber, the negative bias voltage of the argon glow discharge is set to 140 V-160 V, the current of the Cr target arc discharge is set to 110 A-130 A, and the magnetic field coil current is set to 4 A-6 A;
[0045] (52) A metallic Cr intermediate layer is deposited on the surface of the CrN base layer for 40 min to 55 min.
[0046] Further preferably, in step (51), the stainless steel bipolar plate is maintained at 350° C., the argon flow rate is 110 sccm, the negative bias voltage of the argon glow discharge is 150 V, the current of the Cr target arc discharge is 120 A, and the magnetic field coil current is 4 A.
[0047] Further preferably, in step (52), the deposition time of the metal Cr intermediate layer is 40 minutes.
[0048] Preferably, the deposition process of the CrN surface layer comprises the following steps:
[0049] (61) The stainless steel bipolar plate with a metal Cr transition layer, a CrN bottom layer and a metal Cr intermediate layer deposited on the surface is maintained at 300-350° C., and nitrogen gas with a flow rate of 70 sccm-90 sccm is introduced into the coating chamber. The negative bias voltage of the nitrogen glow discharge is set to 140 V-160 V, the current of the Cr target arc discharge is set to 80 A-100 A, and the current of the magnetic field coil is set to 4 A-6 A;
[0050] (62) A CrN surface layer is deposited on the surface of the metallic Cr intermediate layer for 35 min to 45 min.
[0051] Further preferably, in step (61), the stainless steel bipolar plate is maintained at 350° C., the nitrogen flow rate is 80 sccm, the negative bias voltage of the nitrogen glow discharge is 150 V, the current of the Cr target arc discharge is 90 A, and the magnetic field coil current is 6 A.
[0052] Further preferably, the deposition time of the CrN surface layer in step (62) is 40 minutes.
[0053] Preferably, after the CrN surface layer deposition is completed (after the coating is completed), the stainless steel bipolar plate is taken out after being cooled to 50° C. to 100° C. in the furnace.
[0054] More preferably, the stainless steel bipolar plate is taken out after being cooled to 50° C. in the furnace.
[0055] Surface coating treatment can improve the corrosion resistance and conductivity of metal plates, and promote the commercial application of stainless steel metal bipolar plates for hydrogen fuel cells. Due to their good conductivity, chemical stability and excellent hardness, metal materials can provide strong corrosion resistance and improve conductivity for bipolar plates when used as metal bipolar plate coating materials. For example, the tantalum (Ta) coating has a dense structure and can effectively protect the substrate. Its interface contact resistance is about 1 / 10 of that of bare 316L stainless steel. Niobium (Nb) coating can effectively protect stainless steel bipolar plates and reduce the corrosion rate of stainless steel bipolar plates by 50 times. When gold (Au) is coated on the surface of bipolar plates made of 316L stainless steel, it is found that the Au coating can not only effectively improve the corrosion resistance of the bipolar plate, but also significantly improve its elongation at break. Although inert metal coatings can provide excellent conductivity and corrosion resistance, they are relatively expensive and difficult to obtain, which limits their large-scale application. In addition, although the nano precious metal coating has acceptable cost and performance, it is difficult to achieve the performance requirements of DOE2025 due to its thin coating, and it is difficult to become an anti-corrosion coating suitable for metal bipolar plates. Therefore, it is necessary to find abundant resources and low-cost materials as anti-corrosion coating materials for metal bipolar plates, such as alloys, metal carbides, metal nitrides, etc.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] 1. The present invention provides a corrosion-resistant and conductive coating for a hydrogen fuel cell stainless steel bipolar plate, which can solve the problems of poor corrosion resistance and insufficient conductivity of the stainless steel bipolar plate in the acidic environment of the hydrogen fuel cell.
[0058] 2. The CrN coating shows a tendency of columnar crystal growth, and the present invention can inhibit the growth of columnar crystals through a multilayered structural design, making the grains finer. Such a structure makes the coating denser and more bonded, thereby improving the corrosion resistance of the coating. In addition, the multilayer structure design can prevent cracks inside the coating from expanding along the grain boundaries, inhibit the dislocation movement of the crystals, avoid pore connectivity, and prevent the corrosive solution from eroding the inside of the coating through surface defects (such as pores and pinholes) of the coating.
[0059] 3. Compared with stainless steel bipolar plates, the coating of the present invention exhibits high polarization resistance, corrosion potential, and low corrosion current density, has relatively excellent corrosion resistance, and can further reduce the corrosion rate of stainless steel bipolar plates.
[0060] 4. Compared with stainless steel bipolar plates, the coating of the present invention can significantly reduce the interfacial contact resistance (ICR) between the stainless steel bipolar plate and the gas diffusion layer, and maintain a low ICR between the corroded stainless steel bipolar plate and the gas diffusion layer, which helps to improve the conductivity of the stainless steel bipolar plate for long-term service in a hydrogen fuel cell environment.
[0061] 5. The present invention adopts a multilayer structure design with metal Cr as a transition layer, metal ceramic CrN as a bottom layer, metal Cr as an intermediate layer and metal ceramic CrN as a surface layer, which not only improves the bonding strength between the coating and the surface of the stainless steel bipolar plate, but also releases the growth stress of the coating, prolongs the crack expansion distance, and makes the coating have good toughness and thermal shock resistance, thereby improving the surface performance of the stainless steel bipolar plate and prolonging its service life.
[0062] 6. The composite coating of the present invention can improve the durability of the stainless steel bipolar plate in an acidic working environment, enhance the corrosion resistance and electrical conductivity of the stainless steel bipolar plate, and improve the power density of the fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 It is a schematic diagram of the structure of the composite coating of the present invention.
[0064] Figure 2 Surface scanning electron microscope images of the corrosion-resistant and conductive coatings of the hydrogen fuel cell stainless steel bipolar plates prepared in Example 1 and Comparative Examples 1-2.
[0065] Figure 3 Polarization resistance diagram (ohm) of the corrosion-resistant and conductive coating of the hydrogen fuel cell stainless steel bipolar plate prepared in Example 1 and Comparative Examples 1, 2, 4, 5, and 6.
[0066] Figure 4 The following are scanning electron microscope images of the cross sections of the coatings prepared in Example 1 and Comparative Example 3.
[0067] Figure 5 This is a power density diagram of the coated bipolar plate prepared in Example 1 and the uncoated bipolar plate. DETAILED DESCRIPTION
[0068] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0069] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0070] A composite coating on the surface of a hydrogen fuel cell stainless steel bipolar plate, such as Figure 1 As shown, it includes a metal Cr transition layer, a CrN bottom layer, a metal Cr middle layer and a CrN surface layer which are sequentially arranged on the stainless steel bipolar plate.
[0071] The metal Cr transition layer, the CrN bottom layer, the metal Cr intermediate layer and the CrN surface layer are all prepared by the cathode arc + glow discharge technology in the physical vapor deposition technology.
[0072] The raw materials for preparing the metal Cr transition layer, the CrN bottom layer, the metal Cr intermediate layer and the CrN surface layer are argon (Ar) and nitrogen (N2) with a purity of 99.99%, and a metal Cr target with a purity of 99.95%.
[0073] A method for preparing the composite coating on the surface of the above-mentioned hydrogen fuel cell stainless steel bipolar plate, the specific process is as follows:
[0074] During the preparation of the metal Cr transition layer, the temperature is 300-350°C, the argon flow rate is 80sccm-100sccm, the negative bias voltage is 190V-210V, the Cr target current is 100A-120A, the magnetic field coil current is 4A-6A, and the deposition time is 10min-15min.
[0075] During the preparation of the CrN bottom layer, the temperature is 300-350°C, the nitrogen flow rate is 90sccm-120sccm, the negative bias voltage is 110V-130V, the Cr target current is 110A-130A, the magnetic field coil current is 4A-6A, and the deposition time is 35min-45min.
[0076] During the preparation of the metal Cr intermediate layer, the temperature is 300-350°C, the argon flow rate is 100sccm-120sccm, the negative bias voltage is 140V-160V, the Cr target current is 110A-130A, the magnetic field coil current is 4A-6A, and the deposition time is 45min-55min.
[0077] During the preparation of the metal CrN surface layer, the temperature is 300-350°C, the nitrogen flow rate is 70sccm-90sccm, the negative bias voltage is 140V-160V, the Cr target current is 80A-100A, the magnetic field coil current is 4A-6A, and the deposition time is 35min-45min.
[0078] The following describes it in detail with reference to specific embodiments.
[0079] Example 1
[0080] The corrosion-resistant and conductive coating of the stainless steel bipolar plate of the hydrogen fuel cell comprises a metal Cr transition layer, a CrN bottom layer, a metal Cr middle layer and a CrN surface layer which are sequentially arranged on the stainless steel bipolar plate, and the total deposition time of the coating is 130 minutes.
[0081] The preparation process of the above coating is as follows:
[0082] S1: Cleaning: Prepare a mixed aqueous solution of 0.2wt% potassium phosphate, 0.25wt% triethanolamine, and 0.2wt% fatty acid polyoxyethylene ester, and heat it to 60°C; immerse the stainless steel bipolar plate in the prepared aqueous solution, and perform ultrasonic oscillation cleaning on it for 30 minutes to remove surface adhesives; then immerse the stainless steel bipolar plate in 50°C deionized water, and perform ultrasonic oscillation cleaning on it for 20 minutes to remove the aqueous solution residue on its surface; finally, take out the stainless steel bipolar plate, quickly remove the water stains on its surface and dry it.
[0083] S2: Ion etching cleaning: The stainless steel bipolar plate after surface pretreatment is clamped into the coating chamber, and the distance between the stainless steel bipolar plate and the coating target is fixed at 15 cm; after the vacuum degree of the coating chamber is evacuated to 0.4 Pa, the stainless steel bipolar plate is heated to 350°C; then argon gas with a flow rate of 140 sccm is introduced into the coating chamber, the negative bias voltage of the argon glow discharge is 800 V, the current of the Cr target arc discharge is 130 A, and the current of the magnetic field coil is 8 A; the ion etching time is 25 min.
[0084] S3: Preparation of metal Cr transition layer: The stainless steel bipolar plate is maintained at 350°C, the argon flow rate is 90 sccm, the negative bias of the argon glow discharge is 200V, the current of the Cr target arc discharge is 110A, and the magnetic field coil current is 6A; the metal Cr transition layer deposition time is 10min.
[0085] S4: Preparation of CrN bottom layer: The stainless steel bipolar plate is maintained at 350°C, the nitrogen flow rate is 110 sccm, the negative bias of the nitrogen glow discharge is 120V, the current of the Cr target arc discharge is 120A, and the magnetic field coil current is 6A; the deposition time of the CrN bottom layer is 40min.
[0086] S5: Preparation of metal Cr intermediate layer: The stainless steel bipolar plate is maintained at 350°C, the argon flow rate is 110 sccm, the negative bias of the argon glow discharge is 150V, the current of the Cr target arc discharge is 120A, and the magnetic field coil current is 4A; the metal Cr intermediate layer deposition time is 40min.
[0087] S6: Preparation of CrN surface layer: The stainless steel bipolar plate is maintained at 350°C, the nitrogen flow rate is 80 sccm, the negative bias of the nitrogen glow discharge is 150V, the current of the Cr target arc discharge is 90A, and the magnetic field coil current is 6A; the deposition time of the CrN surface layer is 40min.
[0088] S7: After the coating is completed, the stainless steel bipolar plate is cooled to 50° C. in the furnace and taken out. The prepared coating is recorded as CrN / Cr / CrN.
[0089] Example 2
[0090] The corrosion-resistant and conductive coating of the stainless steel bipolar plate of the hydrogen fuel cell comprises a metal Cr transition layer, a CrN bottom layer, a metal Cr middle layer and a CrN surface layer which are sequentially arranged on the stainless steel bipolar plate, and the total deposition time of the coating is 130 minutes.
[0091] The preparation process of the above coating is as follows:
[0092] S1: Cleaning: Prepare a mixed aqueous solution of 0.2wt% potassium phosphate, 0.25wt% triethanolamine, and 0.2wt% fatty acid polyoxyethylene ester, and heat it to 60°C; immerse the stainless steel bipolar plate in the prepared aqueous solution, and perform ultrasonic oscillation cleaning on it for 30 minutes to remove surface adhesives; then immerse the stainless steel bipolar plate in 50°C deionized water, and perform ultrasonic oscillation cleaning on it for 20 minutes to remove the aqueous solution residue on its surface; finally, take out the stainless steel bipolar plate, quickly remove the water stains on its surface and dry it.
[0093] S2: Ion etching cleaning: The stainless steel bipolar plate after surface pretreatment is clamped into the coating chamber, and the distance between the stainless steel bipolar plate and the coating target is fixed at 15 cm; after the vacuum degree of the coating chamber is evacuated to 0.4 Pa, the stainless steel bipolar plate is heated to 350°C; then argon gas with a flow rate of 140 sccm is introduced into the coating chamber, the negative bias voltage of the argon glow discharge is 800 V, the current of the Cr target arc discharge is 130 A, and the current of the magnetic field coil is 8 A; the ion etching time is 25 min.
[0094] S3: Preparation of metal Cr transition layer: The stainless steel bipolar plate is maintained at 350°C, the argon flow rate is 90 sccm, the negative bias of the argon glow discharge is 200V, the current of the Cr target arc discharge is 110A, and the magnetic field coil current is 6A; the metal Cr transition layer deposition time is 10min.
[0095] S4: Preparation of CrN bottom layer: The stainless steel bipolar plate is maintained at 350°C, the nitrogen flow rate is 110sccm, the negative bias of the nitrogen glow discharge is 120V, the current of the Cr target arc discharge is 110A, and the magnetic field coil current is 4A; the deposition time of the CrN bottom layer is 40min.
[0096] S5: Preparation of metal Cr intermediate layer: The stainless steel bipolar plate is maintained at 350°C, the argon flow rate is 110 sccm, the negative bias of the argon glow discharge is 150 V, the current of the Cr target arc discharge is 110 A, and the magnetic field coil current is 6 A; the metal Cr intermediate layer deposition time is 40 min.
[0097] S6: Preparation of CrN surface layer: The stainless steel bipolar plate is maintained at 350°C, the nitrogen flow rate is 80 sccm, the negative bias of the nitrogen glow discharge is 150V, the current of the Cr target arc discharge is 80A, and the magnetic field coil current is 4A; the deposition time of the CrN surface layer is 40min.
[0098] Example 3
[0099] The corrosion-resistant and conductive coating of the stainless steel bipolar plate of the hydrogen fuel cell comprises a metal Cr transition layer, a CrN bottom layer, a metal Cr middle layer and a CrN surface layer which are sequentially arranged on the stainless steel bipolar plate, and the total deposition time of the coating is 130 minutes.
[0100] The preparation process of the above coating is as follows:
[0101] S1: Cleaning: Prepare a mixed aqueous solution of 0.2wt% potassium phosphate, 0.25wt% triethanolamine, and 0.2wt% fatty acid polyoxyethylene ester, and heat it to 60°C; immerse the stainless steel bipolar plate in the prepared aqueous solution, and perform ultrasonic oscillation cleaning on it for 30 minutes to remove surface adhesives; then immerse the stainless steel bipolar plate in 50°C deionized water, and perform ultrasonic oscillation cleaning on it for 20 minutes to remove the aqueous solution residue on its surface; finally, take out the stainless steel bipolar plate, quickly remove the water stains on its surface and dry it.
[0102] S2: Ion etching cleaning: The stainless steel bipolar plate after surface pretreatment is clamped into the coating chamber, and the distance between the stainless steel bipolar plate and the coating target is fixed at 15 cm; after the vacuum degree of the coating chamber is evacuated to 0.4 Pa, the stainless steel bipolar plate is heated to 350°C; then argon gas with a flow rate of 140 sccm is introduced into the coating chamber, the negative bias voltage of the argon glow discharge is 800 V, the current of the Cr target arc discharge is 130 A, and the current of the magnetic field coil is 8 A; the ion etching time is 25 min.
[0103] S3: Preparation of metal Cr transition layer: The stainless steel bipolar plate is maintained at 350°C, the argon flow rate is 90 sccm, the negative bias of the argon glow discharge is 200V, the current of the Cr target arc discharge is 110A, and the magnetic field coil current is 6A; the metal Cr transition layer deposition time is 10min.
[0104] S4: Preparation of CrN bottom layer: The stainless steel bipolar plate is maintained at 350°C, the nitrogen flow rate is 130sccm, the negative bias of the nitrogen glow discharge is 120V, the current of the Cr target arc discharge is 110A, and the magnetic field coil current is 6A; the deposition time of the CrN bottom layer is 40min.
[0105] S5: Preparation of metal Cr intermediate layer: The stainless steel bipolar plate is maintained at 350°C, the argon flow rate is 110 sccm, the negative bias of the argon glow discharge is 150V, the current of the Cr target arc discharge is 130A, and the magnetic field coil current is 6A; the metal Cr intermediate layer deposition time is 40min.
[0106] S6: Preparation of CrN surface layer: The stainless steel bipolar plate is maintained at 350°C, the nitrogen flow rate is 80 sccm, the negative bias of the nitrogen glow discharge is 150V, the current of the Cr target arc discharge is 100A, and the magnetic field coil current is 6A; the deposition time of the CrN surface layer is 40min.
[0107] Related features:
[0108] 1. Surface morphology:
[0109] The surface morphology of the CrN / Cr / CrN coating prepared in Example 1 was compared and characterized. Figure 2 As shown in the figure, it can be seen that the CrN / Cr / CrN multilayer coating has a more complete surface than the Cr / CrN / Cr coating, with fewer surface defects, and is denser and smoother, which plays an important role in further improving the corrosion resistance of stainless steel bipolar plates.
[0110] Among them, the representation objects also include:
[0111] 1) The coating preparation method of Example 1 was adopted, and the coating preparation order was: S1→S2→S3→S5→S4→S5, that is, the structure of the coating was: metal Cr transition layer / metal Cr bottom layer / CrN middle layer / metal Cr surface layer, and the prepared coating was recorded as Cr / CrN / Cr (Comparative Example 1).
[0112] 2) The coating preparation method of Example 1 was adopted, and the metal Cr target with a purity of 99.95% used to prepare the coating was replaced with a metal Ti target with a purity of 99.95%. The preparation order of the coating was: S1→S2→S3→S4→S5→S6, that is, the structure of the coating was: metal Ti transition layer / TiN bottom layer / metal Ti intermediate layer / TiN surface layer, and the prepared coating was recorded as TiN / Ti / TiN (Comparative Example 2).
[0113] 3) The coating preparation method of Example 1 was adopted, and the coating preparation order was: S1→S2→S3→S4, the deposition time of S4 was 120 min, that is, the structure of the coating was: metal Cr transition layer / CrN surface layer, and the prepared coating was recorded as CrN (Comparative Example 3).
[0114] 4) The coating preparation method of Example 1 was adopted, except that the nitrogen gas with a purity of 99.99% used to prepare the coating was replaced with acetylene gas with a purity of 99.99%, that is, the structure of the coating was: metal Cr transition layer / CrC bottom layer / metal Cr middle layer / CrC surface layer, and the prepared coating was recorded as CrC / Cr / CrC (Comparative Example 4).
[0115] 5) The coating preparation method of Example 1 was used, and the coating preparation sequence was: S1→S2→S3→S4→S6. In step S6, acetylene gas with a flow rate of 50 sccm and a purity of 99.99% was introduced. The time of step S6 was 80 min. The prepared coating was recorded as CrN / CrCN (Comparative Example 5)
[0116] 6) The coating preparation method of Example 1 was used, and the coating preparation sequence was: S1→S2→S3→S4→S6. In step S6, acetylene gas with a flow rate of 50 sccm and a purity of 99.99% was introduced, and a metal Ti target with a purity of 99.95% was used. The current of the metal Ti target was 110 A, and the time of step S6 was 80 min. The prepared coating was recorded as CrN / CrTiCN (Comparative Example 6)
[0117] 2. Corrosion resistance:
[0118] Prepare sulfuric acid (H2SO4) with a concentration of 0.5 mol / L and fluoride ion (F - ) concentration is 2ppm, and the prepared mixed solution is heated to 60°C in a water bath. The CrN / Cr / CrN coating prepared in Example 1, and the Cr / CrN / Cr coating, TiN / Ti / TiN coating, CrC / Cr / CrC coating, CrN / CrCN coating, and CrN / CrTiCN coating prepared in Comparative Examples 1, 2, 4, 5, and 6 are subjected to electrochemical corrosion experiments simulating the working environment of a hydrogen fuel cell. The potential range is -0.6V—+1.2V, and the scanning rate is 1mV / s. After fitting by the Tafel extrapolation method, the polarization resistance (ohm, Ω) of the CrN / Cr / CrN coating, Cr / CrN / Cr coating, TiN / Ti / TiN coating, CrC / Cr / CrC coating, CrN / CrCN coating, and CrN / CrTiCN coating is calculated as follows: Figure 3 As shown, the polarization resistance of the CrN / Cr / CrN coating is much greater than that of the Cr / CrN / Cr and TiN / Ti / TiN coatings, and has excellent corrosion resistance in the hydrogen fuel cell environment.
[0119] 3. Conductive properties:
[0120] Under the assembly pressure (1.4MPa) of the hydrogen fuel cell stack, the interface contact resistance test was conducted on the CrN / Cr / CrN coating prepared in Example 1, and the Cr / CrN / Cr coating, TiN / Ti / TiN coating, CrC / Cr / CrC coating, CrN / CrCN coating, and CrN / CrTiCN coating stainless steel bipolar plates prepared in Comparative Examples 1, 2, 4, 5, and 6, to simulate the interface contact between the gas diffusion layer (GDL) and the stainless steel bipolar plate. The experiment is described as follows: First, the stainless steel bipolar plates with the above three coatings were coated with hydrophilic Toray carbon paper (Toray TGP-H-060); then, the carbon paper coated stainless steel bipolar plate was horizontally placed in the middle of a pure copper pressure head; finally, the gold-plated pure copper pressure head applied a load of 1.4MPa to the carbon paper coated stainless steel bipolar plate at a speed of 5mm / min. Under a load of 1.4 MPa, the order of the interfacial contact resistance of the stainless steel bipolar plates with CrN / Cr / CrN coating, Cr / CrN / Cr coating, TiN / Ti / TiN coating, CrC / Cr / CrC coating, CrN / CrCN coating, and CrN / CrTiCN coating is: stainless steel bipolar plate > Cr / CrN / Cr > CrN / CrCN > CrN / CrTiCN > CrC / Cr / CrC > TiN / Ti / TiN > CrN / Cr / CrN. Therefore, the CrN / Cr / CrN coating can improve the conductivity of the bipolar plate in a hydrogen fuel cell environment.
[0121] Chromium carbide is a ceramic material with high hardness, good wear resistance and corrosion resistance. Chromium nitride is similar to chromium carbide and also has excellent mechanical and chemical properties. The conductivity of chromium nitride may be affected by its crystal structure and electronic conduction mechanism, but chromium nitride may have better conductivity than chromium carbide. From the perspective of conductivity, chromium nitride (CrN) may have relatively good conductivity, especially in application scenarios that require good conductivity. Previous experimental research results have shown that at 1 mol·L -1 In NaOH solution, the corrosion resistance of TiN film is about twice that of 201 stainless steel, while the corrosion resistance of CrN film is 24 times that of 201 stainless steel and 12 times that of TiN film. -1 In H2SO4 solution, the corrosion resistance of TiN film and CrN film is 20 times and 26 times higher than that of 201 stainless steel, respectively. Therefore, CrN / Cr / CrN coating shows better corrosion resistance than TiN / Ti / TiN coating.
[0122] The present invention uses cathodic arc ion plating technology to sequentially prepare a metal Cr transition layer, a CrN bottom layer, a metal Cr intermediate layer, and a CrN surface layer on the surface of a stainless steel bipolar plate. In terms of corrosion resistance, compared with a single CrN coating, the growth of columnar crystal structure CrN in the CrN / Cr / CrN coating with a multilayer structure is significantly inhibited, and the relative content is significantly reduced (e.g. Figure 4 As shown), the number of channels through which the acidic corrosive liquid of the hydrogen fuel cell penetrates into the bipolar plate is reduced, thereby improving the corrosion resistance of the stainless steel bipolar plate in the fuel cell environment. In addition, the multi-layered structural design also sets a barrier for the flow of corrosive liquids, which helps to improve the acid corrosion resistance of the stainless steel bipolar plate. Therefore, the CrN / Cr / CrN coating exhibits high polarization impedance and low corrosion current density. In terms of conductivity, the interfacial contact resistance (ICR) values of the CrN / Cr / CrN coated stainless steel are lower than those of the CrN coated stainless steel and the uncoated stainless steel, showing relatively excellent conductivity. The present invention can contribute to the improvement of the working durability and power density of hydrogen fuel cells.
[0123] 4. Power density:
[0124] The bipolar plates in the battery were replaced with the CrN / Cr / CrN coated 316L stainless steel bipolar plates and uncoated 316L stainless steel bipolar plates prepared in Example 1 to investigate the working performance of the CrN / Cr / CrN coating in an actual fuel cell and test the changes in current density and power density. Figure 5 As shown in the figure, the peak power density of the CrN / Cr / CrN coated 316L stainless steel bipolar plate battery is significantly higher than that of the uncoated 316L stainless steel bipolar plate. The uncoated 316L stainless steel bipolar plate has a current density of about 80mA / cm 2 The peak power density reached 25kW / cm 2 , while the coated 316L stainless steel has not yet reached the peak power density. The reason for this phenomenon is mainly attributed to the fact that the contact resistance of the CrN / Cr / CrN coating is much smaller than that of the 316L stainless steel, which can reduce the power loss of the fuel cell and improve the power density of the fuel cell.
[0125] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A composite coating on the surface of a hydrogen fuel cell stainless steel bipolar plate, characterized in that: It includes a metal Cr transition layer, a CrN bottom layer, a metal Cr middle layer and a CrN surface layer which are sequentially arranged on a stainless steel bipolar plate.
2. The composite coating on the surface of the hydrogen fuel cell stainless steel bipolar plate according to claim 1, characterized in that: The thickness of the metal Cr transition layer is 0.08-0.13 μm, the thickness of the CrN bottom layer is 0.35-0.45 μm, the thickness of the metal Cr intermediate layer is 0.32-0.44 μm, and the thickness of the CrN surface layer is 0.35-0.45 μm.
3. A method for preparing a composite coating on the surface of a hydrogen fuel cell stainless steel bipolar plate according to claim 1, characterized in that: A metal Cr transition layer, a CrN bottom layer, a metal Cr middle layer and a CrN surface layer are sequentially deposited on the stainless steel bipolar plate by physical vapor deposition.
4. The method for preparing the composite coating on the surface of the hydrogen fuel cell stainless steel bipolar plate according to claim 3, characterized in that: The stainless steel bipolar plate is sequentially subjected to surface pretreatment and ion etching cleaning.
5. The method for preparing the composite coating on the surface of the hydrogen fuel cell stainless steel bipolar plate according to claim 4, characterized in that: The surface pretreatment comprises the following steps: (11) preparing an aqueous solution containing 0.15 wt % to 0.3 wt % of potassium phosphate, 0.2 wt % to 0.3 wt % of triethanolamine, and 0.15 wt % to 0.3 wt % of fatty acid polyoxyethylene ester; (12) heating the prepared aqueous solution to 50° C.-60° C.; (13) Immerse the stainless steel bipolar plate in the prepared aqueous solution and perform ultrasonic cleaning for 20 min to 30 min to remove surface adhesives; (14) After ultrasonic cleaning, immerse the stainless steel bipolar plate in deionized water at 50° C. to 60° C. and perform ultrasonic oscillation cleaning on the plate for 20 min to 30 min to remove the residual aqueous solution on the surface. (15) Take out the stainless steel bipolar plate, remove the water stains on its surface and dry it.
6. The method for preparing the composite coating on the surface of the hydrogen fuel cell stainless steel bipolar plate according to claim 4, characterized in that: The ion etching cleaning comprises the following steps: (21) Clamping the surface pretreated stainless steel bipolar plate into the coating chamber, with the stainless steel bipolar plate being 15 to 20 cm away from the coating target; (22) reducing the vacuum degree of the coating chamber to below 0.5 Pa; (23) heating the stainless steel bipolar plate to 300-350° C.; (24) introducing argon gas at a flow rate of 120 sccm to 150 sccm into the coating chamber, setting the negative bias voltage of the argon glow discharge to 700 V to 800 V, setting the current of the Cr target arc discharge to 120 A to 150 A, and setting the current of the magnetic field coil to 7 A to 9 A; (25) Ion etching for 25 min to 30 min.
7. The method for preparing the composite coating on the surface of the hydrogen fuel cell stainless steel bipolar plate according to claim 3, characterized in that: The deposition process of the metal Cr transition layer comprises the following steps: (31) The stainless steel bipolar plate is maintained at 300-350° C., argon gas with a flow rate of 80 sccm-100 sccm is introduced into the coating chamber, the negative bias voltage of the argon glow discharge is set to 190 V-210 V, the current of the Cr target arc discharge is set to 100 A-120 A, and the magnetic field coil current is set to 4 A-6 A; (32) A metal Cr transition layer is deposited on the surface of the stainless steel bipolar plate for 10 min to 15 min.
8. The method for preparing the composite coating on the surface of the hydrogen fuel cell stainless steel bipolar plate according to claim 3, characterized in that: The deposition process of the CrN bottom layer includes the following steps: (41) The stainless steel bipolar plate with a metal Cr transition layer deposited on the surface is maintained at 300-350° C., and nitrogen gas with a flow rate of 90 sccm-120 sccm is introduced into the coating chamber. The negative bias voltage of the nitrogen glow discharge is set to 110 V-130 V, the current of the Cr target arc discharge is set to 110 A-130 A, and the current of the magnetic field coil is set to 4 A-6 A; (42) Deposit a CrN base layer on the surface of the metal Cr transition layer for 35 min to 45 min.
9. The method for preparing the composite coating on the surface of the hydrogen fuel cell stainless steel bipolar plate according to claim 3, characterized in that: The deposition process of the metal Cr intermediate layer comprises the following steps: (51) The stainless steel bipolar plate with a metal Cr transition layer and a CrN bottom layer deposited on the surface is maintained at 300-350° C. Argon gas with a flow rate of 100 sccm-120 sccm is introduced into the coating chamber, the negative bias voltage of the argon glow discharge is set to 140 V-160 V, the current of the Cr target arc discharge is set to 110 A-130 A, and the magnetic field coil current is set to 4 A-6 A; (52) A metallic Cr intermediate layer is deposited on the surface of the CrN base layer for 40 min to 55 min.
10. The method for preparing the composite coating on the surface of the hydrogen fuel cell stainless steel bipolar plate according to claim 3, characterized in that: The deposition process of the CrN surface layer comprises the following steps: (61) The stainless steel bipolar plate with a metal Cr transition layer, a CrN bottom layer and a metal Cr intermediate layer deposited on the surface is maintained at 300-350° C., and nitrogen gas with a flow rate of 70 sccm-90 sccm is introduced into the coating chamber. The negative bias voltage of the nitrogen glow discharge is set to 140 V-160 V, the current of the Cr target arc discharge is set to 80 A-100 A, and the current of the magnetic field coil is set to 4 A-6 A; (62) Depositing a CrN surface layer on the surface of the metallic Cr intermediate layer for 35 min to 45 min; After the CrN surface layer deposition is completed, the stainless steel bipolar plate is taken out after being cooled to 50° C. to 100° C. in the furnace.
Citation Information
Cited By
Metal bipolar plate composite coating and preparation method thereof, metal bipolar plate and fuel cell
CN120511318A